RISK MITIGATION IN PLANNING AND WAREHOUSING ACTIVITIES OF FERTILIZER FACTORY SPARE PARTS (Case Study: PT Pupuk Iskandar Muda) - Anugrah, Ibnu; Hadiguna, Rika Ampuh; Amrina, Elita (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
In meeting the needs of spare parts in a supply chain, the warehouse is one of the most important parts. Warehouses have three main processes, namely receiving, storing, and distributing so, warehouse needs are certainly very important to help companies achieve their goals. This research uses an integrated Fuzzy Logic, House of Risk (HOR), and Supply Chain Operation Reference (SCOR) approach. Interviews, focus discussion groups, and questionnaires are the data collection methods used. From the results of data processing, 19 risk events and 27 risk agents were obtained. From the results of the pareto diagram, 14 risk agents were selected to focus on risk mitigation and have the ability to direct the reduction of risk. Furthermore, 14 risk agents were developed into 28 mitigation strategies and there were 10 prioritized risk mitigation strategies. Keywords: Risk Mitigation, Warehousing, SCOR, HOR, Fuzzy Logic, Pareto Diagram.